Flexible Ionic Conjugated Microporous Polymer Membranes for Fast and Selective Ion Transport. (27th October 2021) - Zhou, Zongyao; Shinde, Digambar B.; Guo, Dong; Cao, Li; Nuaimi, Reham Al; Zhang, Yuting; Enakonda, Linga Reddy; Lai, Zhiping
Abstract: Membranes with fast and selective ion transport have great potential for use in water‐ and energy‐related applications. The structure and material design of the membranes play a key role in improving their performance. Conjugated microporous polymers (CMPs) as emerging membrane materials have shown uniform pore size, high surface area, and excellent chemical stability, but their mechanical properties are poor due to their brittleness. Herein, a flexible ionic CMP membrane with precisely tailored pore architecture and chemistry prepared by a coelectropolymerization (COEP) strategy is reported. The structure contains rigid monomers to maintain structural uniformity and flexible and charged monomers to enhance mechanical flexibility and improve ion selectivity by combining precise size sieving and Donnan effect. The resulting 40 nm thick CMP membranes show equivalent ion conductance compared to the commercial Nafion 117 membrane, but an order of magnitude higher ion selectivity for ion systems such as K + /Mg 2+ and Li + /Mg 2+ . Abstract : The strategy of coelectropolymerization (COEP) achieves dual softness and functionalization adjustments to conjugated microporous polymer (CMP) membranes. The flexible ionic 40 nm thick membranes enable fast transport of monovalent ions and high selectivity toward divalent ions.